Tetralogy of Fallot with Absent Pulmonary Valve - A Case Report - Rahman, Md Mazibur (University Heart Journal, 2011)
A 25 years male patient of Tetralogy of Fallot (TOF) with congenital absent of pulmonary valve (APV) presented with symptoms of palpitation and exertional respiratory distress without congestive heart failure. He underwent successful repair of intracardiac defects. The procedures consisted of patch closure of ventricular septal defect and right. ventricular outflow tract reconstruction with a monocusp transannular patch. Resection or plication of dilated pulmonary artery was not required. The patient is doing well without any symptoms. Key words: Tetralogy of Fallot; Absent pulmonary valve DOI: 10.3329/uhj.v6i1.7197 University Heart Journal Vol.6(1) 2010 pp.48-50